Rancang Bangun Aplikasi File Transfer Menggunakan Library ZeroMQ - Pawitra, I Gusti Ngurah Yoga; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2020)
Sending data with large data sizes between two or more computers in a company is affected by various factors, both the network connection of the two computers to the data exchange method used, one method that can be used is the ZeroMQ library. The method of sending files using the ZeroMQ method is relatively faster because the architecture is brokerless or without middleware as an intermediary so that the process of sending files can be done quickly and can blow up the resources used. The ZeroMQ method was originally created to send messages, but we can add file conversion algorithms to binary numbers, so the messages sent are binary numbers from encoded files. This application is built on the Python programming language so that it is easier to develop again. The results of the design of file transfer applications using the ZeroMQ library performed on two server computers and client computers explain that this method can be used to send files and from the results of the test the time required and the latency value is relatively faster and more stable.